The quest [compact disc, unabridged] - Smith, Wilbur A. (Smith, Wilbur A. Ancient Egypt series., 2007)
Egypt is struck by a series of terrible plagues that cripple the Kingdom, and then the ultimate disaster follows--the Nile fails. The waters that nourish and sustain the land dry up. Something catastrophic is taking place in the distant and totally unexplored depths of Africa from where the mighty river springs. In desperation Pharaoh sends for Taita, the only man who might be able to win through to the source of the Nile and discover the cause of all their woes. But none have any idea of what a terrible enemy lies in ambush for The Warlock in those mysterious lands at the end of their world.